2020
DOI: 10.18488/journal.137.2020.42.69.79
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Covid-19 on Rural Areas Students of Pakistan: Moderating Role of HEC Policy and Internet Service

Abstract: Covid-19 Issue of rural areas students Internet expenditure HEC policy Pakistan. Contribution/ Originality: The contribution of this study which has investigated the impact of Covid-19 on education of rural area of student: moderating role of HEC policy and internet service in case of Pakistan. This study contributes in Covid-19 literature and gives the solution of problem which Pakistani student face in rural area in case of online classes and internet service. 1. INTRODUCTION First, World Health Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…Our research also demonstrated that students from urban regions were 44% less distressed than pupils of rural areas. This could be attributed to rural students' low socioeconomic status and unsatisfactory internet connections preventing them from attending online classes ( 55 ). Additionally, the lowest-income family students were 1.76 times higher stressed than the students of the highest-income families, that was consistent to the previous findings reported by Sayeed et al ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our research also demonstrated that students from urban regions were 44% less distressed than pupils of rural areas. This could be attributed to rural students' low socioeconomic status and unsatisfactory internet connections preventing them from attending online classes ( 55 ). Additionally, the lowest-income family students were 1.76 times higher stressed than the students of the highest-income families, that was consistent to the previous findings reported by Sayeed et al ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that students with certain predictors (male, first level, low socioeconomic status, and applied sciences) were found to be less satisfied with the online mode of learning [1]. A study in Pakistan stated that students with low socioeconomic status and living in rural areas are unable to attend the classes due to poor signal strength [47]. A study conducted in the Philippines reported that most students are not satisfied with this online mode of learning.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, the first case was tested positive in karachi on February 26, 2020. Pakistan is one of the developing countries in south asian context and is unable to run effectively the virtual education approaches like that are followed by other developed countries China,USA ,EU etc.COVID-19 has poorly affected the education of students belonging to remote areas (Zahra, Gul, Iqbal, Ghafoor, & Ambreen, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%